Analysis of Slipstream Flow in a Wide-necked Basilar Artery Aneurysm: Evaluation of Potential Treatment Regimens - Imbesi, Steven G. (AJNR Am J Neuroradiol, 2001)
Summary: A replica of a lethal wide-necked basilar artery aneurysm was created by casting a deceased patient's brain vessels and then placing the replica in a circuit of pulsating optically clear non-Newtonian fluid. Individual fluid slipstreams were opacified with isobaric dyes, and images were recorded on film. Studies were completed on the vascular replica, then were repeated, first after placement of a stent across the aneurysm neck and then after placement of Guglielmi detachable coils into the aneurysm sac through the stent. The slipstreams entered the untreated aneurysm via the distal aneurysm neck (the inflow zone), impacting against the distal lateral aneurysm wall. When the stent was placed across the aneurysm neck, the slipstreams lost coherence and did not strike the aneurysm sidewall. Placing the coils further disturbed and reduced aneurysmal flow, especially when the coils filled the inflow zone at the distal lateral aneurysm sac.